2022
DOI: 10.1039/d1np00025j
|View full text |Cite
|
Sign up to set email alerts
|

Alternative metabolic pathways and strategies to high-titre terpenoid production inEscherichia coli

Abstract: Terpenoids are a diverse group of chemicals used in a wide range of industries. They can be made through alternative metabolic pathways to reach the higher needed for biomanufacturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 325 publications
0
28
0
Order By: Relevance
“…Prior studies have suggested that instability in titers of terpenoids and other natural products may be due to plasmid recombination events, which in turn reduces in vivo production of toxic intermediates and products generated by full length constructs ( Rinaldi et al, 2021 ). This may be especially relevant for pathways where either large or multiple plasmids need to be maintained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have suggested that instability in titers of terpenoids and other natural products may be due to plasmid recombination events, which in turn reduces in vivo production of toxic intermediates and products generated by full length constructs ( Rinaldi et al, 2021 ). This may be especially relevant for pathways where either large or multiple plasmids need to be maintained.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that linalool significantly affects cell growth rate at levels < 1 g/L, with high concentrations (20 g/L) leading to a rapid loss of cell density after the addition of linalool ( Supplementary Figure S6 ). Therefore, we performed Adaptive Laboratory Evolution (ALE) to increase the tolerance of E. coli DH5α towards linalool by performing continuous cultivation in increasing concentrations of linalool ( Rinaldi et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of enzymes from both natural sources or produced in recombinant form, as raw or highly purified extracts, is also becoming increasingly common [ 7 , 8 , 9 ]. Enzymes can be used in cascades that mimic synthetic biochemical pathways, or they can replace some steps in the total synthesis of natural and non-natural molecules with high structural complexity [ 10 , 11 , 12 , 13 , 14 ]. However, the use of enzymes can be challenging on a large scale due to their high production costs, low operational stability, and difficulties in recovering them from the reaction mixtures [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative pathways, including additional entry points into the MVA and MEP pathways, archaeal MVA pathways, and artificial pathways have also been identified at the sequence level. [6] Prenyl pyrophosphate (prenyl‐PP) synthases catalyse the head‐to‐tail condensation of IPP and DMAPP into prenyl‐PP substrates of varying lengths such as geranyl pyrophosphate (GPP, C 10 ), farnesyl pyrophosphate (FPP, C 15 ), geranylgeranyl pyrophosphate (GGPP, C 20 ) and geranyl‐farnesyl pyrophosphate (GFPP, C 25 ), the pre‐cursors for mono‐, sesqui‐, di‐ and sesterterpenoids, respectively. These prenyl‐PP substrates are converted into structurally diverse terpene scaffolds by terpene synthases (TSs).…”
Section: Introductionmentioning
confidence: 99%